Compliance with Standard Precautions among Midwives during the COVID-19 pandemic - Mergy Gayatri; Oluwadamilare Akingbade; Emmanuel O. Adesuyi; Roland Arung Pirade; Natasha Van Antwerpen; Ningrum Paramita Sari; Sutrisno Sutrisno (Universitas Andalas, 2021)
Background: While the COVID-19 pandemic has spread across nations in significant terms, midwives who play a crucial role in offering maternal and child care amid the pandemic stand a high risk of being infected. Examining their level of compliance with the standard precautions amid the pandemic is important.Purpose: To assess the level of compliance of midwives in Indonesia with Personal Protective Equipment (PPE) usage and hand washing.Methods: In June 2020, an online cross-sectional survey was conducted on 1520 midwives in Indonesia during the early onset of the COVID-19 pandemic. Data were analyzed using Statistical Package for the Social Sciences version 26. Association between demographic variables and compliance with standard precautions was measured using Chi-square test. Results: Approximately 74% of midwives used PPE and masks when outside while more than 40% of them did not always wash their hands after they touch an object outside home. A significant association was found between level of education (p =.001), region (p =.000) and mask usage. However, association between ethnicity and mask usage; region and handwashing were not significant. Conclusion: Majority of the midwives in Indonesia complied with PPE usage, but majority did not adhere to hand washing. This highlights the need for appropriate interventions to improve compliance to standard precautions in a bid to curtail further spread of the pandemic.